Effects of ciceritol from chickpeas on human colonic microflora and the production of short chain fatty acids by in vitro fermentation. (June 2017) - Zhang, Yun; Su, Di; He, Jinyan; Dai, Zhuqing; Asad, Riaz; Ou, Shiyi; Zeng, Xiaoxiong
Abstract: The aim of this study was to evaluate the effects of ciceritol on human colonic microflora and the production of short chain fatty acids (SCFAs). Ciceritol was extracted from chickpeas by using 50% ethanol-water solvent with a ratio of 1:10, and the extract was purified by chromatography of charcoal-Celite column and gel chromatography of Biogel P-2 column. Bacterial population and the concentration of SCFAs during in vitro anaerobic fermentation were investigated to evaluate the effect of ciceritol on human colonic microflora. The results indicated that the addition of ciceritol could significantly enhance the growth of Lactobacillus–Enterococcus group (8.26 compared to 7.71 log10 cells/mL of control group) and Bifidobacterium spp. (10.43 compared to 9.45 log10 cells/mL of control group), and inhibit the growth of Bacteroides–Prevotella, Clostridium histolyticum and Eubacterium–Clostridium groups. Besides, the production of SCFAs was significantly improved by addition of ciceritol that the content was twice of the control group. Accordingly, we conclude that ciceritol can behave as a potential prebiotics by optimizing the microflora of human colon and promoting the production of SCFAs, which will benefit to human health. Highlights: Ciceritol could enhance growth of Lactobacillus–Enterococcus and Bifidobacterium spp. Ciceritol could inhibit growth of Bacteroides–Prevotella and C. histolyticum groups. Production of SCFAs was improved by addition of ciceritol. Ciceritol from chickpeas could behave as a potential prebiotics.